Genomic characterization of novel bat kobuviruses in Madagascar: Implications for viral evolution and zoonotic risk - Freddy L. Gonzalez; Gwenddolen Kettenburg; Hafaliana Christian Ranaivoson; Angelo Andrianiaina; Santino Andry; Vololoniaina Raharinosy; Tsiry Hasina Randriambolamanantsoa; Vincent Lacoste; Philippe Dussart; Jean-Michel Héraud; Cara E. Brook (PLoS ONE, 2025)
Kobuviruses (family Picornaviridae , genus Kobuvirus ) are enteric viruses that infect a wide range of both human and animal hosts. Much of the evolutionary history of kobuviruses remains elusive, largely due to limited screening in wildlife. Bats have been implicated as major sources of virulent zoonoses, including coronaviruses, henipaviruses, lyssaviruses, and filoviruses, though much of the bat virome still remains uncharacterized. While most bat virus research has historically focused on immediately recognizable zoonotic clades (e.g., SARS-related coronaviruses), a handful of prior reports catalog kobuvirus carriage in bats and posit the role of bats as progenitors of downstream kobuvirus evolution. As part of a multi-year study, we carried out metagenomic Next Generation Sequencing (mNGS) on fecal samples obtained from endemic, wild-caught Madagascar fruit bats to characterize potentially zoonotic viruses circulating within these populations. The wild bats of Madagascar represent diverse Asian and African phylogeographic histories, presenting a unique opportunity for viruses from disparate origins to mix, posing a significant public health threat. Here, we report detection of kobuvirus RNA in Malagasy fruit bats ( Eidolon dupreanum ) and undertake phylogenetic characterization of Malagasy kobuvirus sequences, which nest within the Aichivirus A clade – a kobuvirus clade known to infect a wide range of hosts including humans, rodents, canids, felids, birds, and bats. Given the propensity of kobuviruses for recombination and cross-species transmission, further characterization of this clade is critical for accurate evaluation of future zoonotic threats.